2019
DOI: 10.1108/ijchm-02-2019-0106
|View full text |Cite
|
Sign up to set email alerts
|

Standing out from the crowd – an exploration of signal attributes of Airbnb listings

Abstract: Purpose -Due to product diversity, traditional quality signals in the hotel industry such as star ratings and brand affiliation do not work well in the accommodation booking process on the sharing economy platform. From a suppliers' perspective, this study aims to apply the signaling theory to the booking of Airbnb listings and explore the influence of quality signals on the odds of an Airbnb listing being booked.Design/methodology/approach -A binomial logistic model is used to describe the influences of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 51 publications
0
43
0
Order By: Relevance
“…The results showed that the overall external BE relies heavily on the physical facility quality, which is tangible, visible, and easy to be recognized by customers. As signaling theory argues, in an immature market, which lacks sufficient information and understanding, customers must seek observable and creditable signals to ensure service quality and overall experience (Yao et al, 2019). Qualities of hotels are traditionally suggested by star rating, facilities, and brand affiliation, which are standardized and identifiable (Oskam and Boswijk, 2016).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…The results showed that the overall external BE relies heavily on the physical facility quality, which is tangible, visible, and easy to be recognized by customers. As signaling theory argues, in an immature market, which lacks sufficient information and understanding, customers must seek observable and creditable signals to ensure service quality and overall experience (Yao et al, 2019). Qualities of hotels are traditionally suggested by star rating, facilities, and brand affiliation, which are standardized and identifiable (Oskam and Boswijk, 2016).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…For the category of price determinants related to host attributes, most previous studies showed that whether the host is a "superhost" can increase accommodation prices [12,15,18,20,32], with a few exceptions [19]. Further, counterintuitively, posting a profile picture of a host has a negative effect on the price [12].…”
Section: Ratingmentioning
confidence: 99%
“…A study using sequential Bayesian [28] aims to understand the booking probability of listings and to know the posterior distribution. Demand forecast is an essential part of revenue management [29] because it maximizes revenue gain [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The predictor variables were based on the findings of previous studies [28] [7] but five predictor variables, namely the number of neighboring listings, available neighboring listings, house rules, property description, and the number of listing pictures were excluded from this study because of data and computing limitations. Instead, we added other variables such as total host listings, host verifications, accommodates, the guests included, minimum nights, and maximum nights.…”
Section: B Choice Of Variablesmentioning
confidence: 99%